Differential Geometry of Manifolds - Lovett, Stephen (Stephen T.) (Milton : CRC Press LLC, 2019)
Differential Geometry of Manifolds, Second Edition presents the extension of differential geometry from curves and surfaces to manifolds in general. The book provides a broad introduction to the field of differentiable and Riemannian manifolds, tying together classical and modern formulations. It introduces manifolds in a both streamlined and mathematically rigorous way while keeping a view toward applications, particularly in physics. The author takes a practical approach, containing extensive exercises and focusing on applications, including the Hamiltonian formulations of mechanics, electromagnetism, string theory. The Second Edition of this successful textbook offers several notable points of revision. New to the Second Edition: New problems have been added and the level of challenge has been changed to the exercises Each section corresponds to a 60-minute lecture period, making it more user-friendly for lecturers Includes new sections which provide more comprehensive coverage of topics Features a new chapter on Multilinear Algebra
Pseudo-Riemannian Manifolds -- 7.3 Electromagnetism -- 7.4 Geometric Concepts in String Theory -- 7.5 Brief Introduction to General Relativity -- A: Point Set Topology -- A.1 Metric Spaces -- A.2 Topological Spaces -- B: Calculus of Variations -- B.1 Formulation of Several Problems -- B.2 Euler-Lagrange Equation -- B.3 Several Dependent Variables -- B.4 Isoperimetric Problems and Lagrange Multipliers -- C: Further Topics in Multilinear Algebra -- C.1 Binet-Cauchy and k-Volume of Parallelepipeds -- C.2 Volume Form Revisited -- C.3 Hodge Star Operator -- Bibliography -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Manifolds (Mathematics); Geometry, Differential; MATHEMATICS / General; MATHEMATICS / Arithmetic; MATHEMATICS / Geometry / General